Exploring primary care physicians’ role in travel medicine: a scoping review of knowledge, practices, and training - Ayman Al-Dahshan; Salma Ahmed; Anwar Joudeh; Vahe Kehyayan (Tropical Diseases, Travel Medicine and Vaccines)
Abstract Background With the surge in international travel, primary care physicians (PCPs) play a critical role in managing travel medicine (TM) challenges. This scoping review aims to comprehensively synthesize literature on PCPs’ involvement in TM, covering their knowledge, practices, and training. Methods Systematic searches across various electronic databases identified empirical studies in English language peer-reviewed journals up to July 2023. Data synthesis involved charting evidence on PCPs’ TM knowledge, practices, and training. Results Sixteen articles met inclusion criteria, offering insights into PCPs’ engagement with TM in primary care. The findings reveal a general deficiency in PCPs’ TM knowledge, with factors like prior TM experience, formal training, high traveler exposure, and multilingual abilities predicting higher knowledge scores. TM consultation duration and documentation were frequently reported as insufficient. Barriers to effective TM provision included physician-related factors such as lack of formal training, traveler-related factors like delayed presentation and low-risk perception, and practice-related factors such as low traveler exposure and resource constraints. Conclusion This review underscores the crucial role of PCPs in TM and the need for targeted interventions to enhance their expertise and practices. Overcoming barriers through tailored training and support is essential for optimizing TM delivery in primary care.